Pembelajaran Fisika Konsep Kalor Dengan Menggunakan Media Pirolisis Sampah Plastik Untuk Meningkatkan Ketrampilan Berpikir Kritis Siswa Di SMAN 3 Bengkulu Tengah - Umi kalsum; Agus Sundaryono; M Farid (PendIPA Journal of Science Education, 2017)
The objectives of this research are (1) to know the value of density, viscosity, fog point, oil absorption caloric, odor, color and fire sensitivity, in pyrolysis of plastic garbage from condenser one and two adsorbed using zeolite and activated charcoal, (2) the content contained in pyrolysis plastic waste oil adsorbed using active zeolite and charcoal, (3) knowing differences in critical thinking skills among students who learn to use guided inquiry learning model with students who study conventionally on physics learning. Convert plastic waste into fuel oil using a pyrolysis process with two water condensers, then plastic waste pyrolysis oil adsorbed using activated zeolite and charcoal. The results showed that the density value of the adsorbed oil for one condenser was 772 Kg / m3 and the condenser was 770 Kg / m3, the viscosity value of the adsorbed oil from the condenser one and two had the same value of 0.49 m2 / s, the fog point value oil that has been adsorbed on the condenser yield one and two is the same value that is -18oC, the calorific value of oil absorption, color, odor, and fire sensitivity shows the more adsorbent and the longer the adsorption process, the oil absorbs the smaller, , the odor does not sting, and the fire sensitivity gets smaller. GC-MS test results obtained the most compounds contained in pyrolysis oil plastic waste that has been adsorbed that is 1,3,5-trimethylcyclohexene. The implementation of physics learning on the concept of heat shows that there are differences in critical thinking skills in control and experiment class. Based on different test on posttest result the first material got 0,022 and postest second material equal to 0,047, the value is smaller than level of significance 0,05 so Ha accepted.